(Inter)subjectification and its limits in secondary grammaticalization. (January 2015) - Narrog, Heiko
Abstract: It is widely accepted that subjectification and intersubjectification are important processes of semantic change accompanying grammaticalization. However, typical changes of subjectification concern early stages of grammaticalization, and the role of subjectification and intersubjectification in late stages of grammaticalization is not yet fully explored. In this paper, I am looking for (1) regular changes other than (inter)subjectification in secondary grammaticalizations, and (2) counter-examples to the hypothesized directionalities of change. In doing so, I mainly look at the development of core case marking, at the development of elements with textual functions, and at presumptive counter-examples from other areas of grammar that have been proposed in the literature. I conclude that (1) the evolution of textual/discourse-functions is a significant development not captured in the canonical (inter-)subjectification scenario both in terms of concept and in terms of directionality, and (2) that de-subjectification and de-intersubjectification in terms of expressive (inter)subjectivity regularly takes place at later stages of grammaticalization. However, this de-(inter)subjectification mainly accompanies the development of highly paradigmatic and abstract meanings, and concerns a loss of subjectivity in terms of expressiveness. On the other hand, since meanings are increasingly appropriated for the expression of speaker-deixis and internal reasoning, the overall directionality of change can still be understood as speaker-, hearer- and text-orientation, and it might not be appropriate to label the overall development as 'de-subjectification' or 'objectification'. Highlights: Secondary grammaticalization often involves a loss of expressive subjectivity. Instead, abstract deicitic speaker-oriented meanings may develop. Furthermore, there is often a development towards textual (discourse) functions. These tendencies are captured by the concept of increased speech-act orientation.